NURSING INTERVENTION GIVING WARM COMPRESS TO LARGE VEINS AREAS WITH ABDOMEN WALLS TO DECREASE TEMPERATURE OF HYPERTHERMIC PATIENTS - Handayani, Risanti; Hariyono; Hargono, Arief (Jurnal Biosains Pascasarjana, 2024)
Intra-abdominal organs are receptors that are more sensitive to temperature, cold. While the large vein area is effective because of the vasodilation process by giving warm compresses to reduce body temperature on the body surface. The purpose of this study was to determine the effectiveness of giving warm compresses to the abdominal wall (abdomen) and large vein (axilla) area to decrease the body temperature in fever patients. The design of this research is Quast-Experiment, Design with Nonequivalent Control Group Design approach. The population of this study was all patients with fever as many as 26 respondents. Samples were taken by consecutive sampling technique as many as 20 patients. The research variable is a warm compress in the axilla and abdomen and the independent variable is a decrease in body temperature. Data were collected by observing body temperature and analyzed by using the T-test. The results showed that abdominal compresses were more effective because the number of patients who did not experience a decrease was 1 respondent, while the axilla compression had 2 respondents. The results of the normality test of the data showed that the data were not normally distributed so that the hypothesis testing used the T-test and the results showed that the data was p = 0.000, = 0.05 so that p < a means Ho is rejected, meaning that the difference in body temperature decrease between giving axillary compresses and abdominal compresses is not too significant. and not that much different. Keywords: Warm Compress, Fever, Body Temperature.